2019
DOI: 10.3759/tropics.ms18-12
|View full text |Cite
|
Sign up to set email alerts
|

Drainage effects on leaf traits of trees in tropical peat swamp forests in Central Kalimantan, Indonesia

Abstract: Large areas of the tropical peat swamp forests in Central Kalimantan were drained to be converted into rice fields and then abandoned. A change in the soil water level due to drainage in the forests must have had a big impact on the ecology and ecophysiology of the trees in the drained remnant forests. The leaf traits of these trees in particular may have been directly or indirectly affected by drainage because of their high sensitivity to environmental change. To understand the influence of drainage on leaf t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
(69 reference statements)
1
2
0
Order By: Relevance
“…In this study, the thicker and higher-LMA leaves observed in both the heterobaric and homobaric species in the upper canopy protect against heat and drought conditions in the forest canopy, consistent with previous studies (Niinemets, 2007;Leigh et al, 2012;Kenzo et al, 2015;Ichie et al, 2019). Furthermore, we found that the increases in thickness and LMA contributed to increased leaf toughness with tree height.…”
Section: Vertical Variations In Leaf Toughness and Leaf Morphological...supporting
confidence: 92%
“…In this study, the thicker and higher-LMA leaves observed in both the heterobaric and homobaric species in the upper canopy protect against heat and drought conditions in the forest canopy, consistent with previous studies (Niinemets, 2007;Leigh et al, 2012;Kenzo et al, 2015;Ichie et al, 2019). Furthermore, we found that the increases in thickness and LMA contributed to increased leaf toughness with tree height.…”
Section: Vertical Variations In Leaf Toughness and Leaf Morphological...supporting
confidence: 92%
“…Total K and P in the litter of all NS were higher than those in litter of Koompassia malaccensis, Shorea uliginosa, and mixed tropical peat forest tree species (Sulistiyanto et al 2005;Ong et al 2017). However, leaf litter of all NS in present study in general had lower N content than that in most of native species of tropical peat swamp forest, despite its value was in the range (0.8-1.78) (Sulistiyanto et al 2005;Ong et al 2017;Ichie et al 2019) Lignin content in the litter of all NS in present study (36.1-39.2%) was higher than that in the range of content lignin in other native tree species of peat swamp forest (3.8-35.8%) (Hoyos-Santillan et al 2015;Ichie et al 2019) also than that in the average of broadleaves (29.26%) and coniferous (21.57%) (Rahman et al 2013). In different ecosystem with wider scale, lignin content of leaf litter of beech (36%) in temperate forest were the closest to lignin content in the NS (Kara et al 2014).…”
Section: Litter Qualitymentioning
confidence: 51%
“…The increased LMA under the open control observed in this study may also have contributed to increased drought tolerance (Kramer 1983;Niinemets 2001). For example, leaves with a high LMA showed higher tolerance to dehydration in a study using dipterocarp species in Malaysia (Kenzo et al 2007), and trees subjected to drought stress using an artificial drain had a significantly larger LMA than those in wet plots in an Indonesian tropical swamp forest (Ichie et al 2019). A large LMA contributes to drought tolerance by increasing the strength of a leaf, because greater physical strength and a thick cell wall promote tolerance of the lower leaf water potential associated with drought stress (Niinemets 2001;Koch et al 2004;Poorter et al 2009).…”
Section: Ecophysiological Traits and Seedling Growthmentioning
confidence: 66%